Peranan Pendidikan Lingkungan Hidup untuk Meningkatkan Pendapatan Kawasan Kebun Raya Massenrempulu Kecamatan Maiwa Kabupaten Enrekang - Hasriyanti; Erman Syarif; Sartina (PT. Lontara Digitech Indonesia, 2024)
Environmental education plays an important role in increasing the understanding and awareness of the community, including visitors, about the urgency of nature conservation in Massenrempulu Botanical Garden. This research aims to identify effective environmental education strategies that can increase the income of the botanical garden area as well as how to develop an environmental education model that can be implemented sustainably. The type of research applied is qualitative with a case study approach. developing Massenrempulu Botanical Garden as an effective and sustainable environmental education centre, there are three main strategies that must be integrated: diversification of funding sources, efficient management of funds, and advocacy for budget increases. These three strategies proved complementary and played an important role in supporting the botanical garden's conservation and education objectives.